Floodplain Chronology and Vertical Sedimentation Rates Along the Red River, Southern Manitoba - Brooks, Gregory (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractThis paper reports the accelerator mass spectrometry radiocarbon ages and geomorphic context of one bone and 38 charcoal samples collected from 12 floodplain exposures along the Red River, southern Manitoba. The stratigraphically oldest dates range from 3760 to 6710 cal BP and indicate that floodplain deposits of at least mid-Holocene age are preserved along the valley bottom. The average rate of lateral channel migration at the meander adjacent to section Ju30-1-98 is up to 0.08 m a-1 over the past 3850 years. In sections Se04-1-97, Ju30-1-98, Ju23-1-98 and Ju21-2-98, the rates of vertical sedimentation above and below 1 to 3 m depth, range from 0.3 to 0.8 mm a-1 and 1.7 to 3.7 mm a-1, respectively. The decease in sedimentation rates is interpreted to represent a shift from oblique accretion/proximal overbank sedimentation to distal overbank sedimentation. In sections Ju28-1-98, Au05-1-00, Au03-1-98 and Ju21-1-98, which are late Holocene in age, the average rates of vertical sedimentation range from 1.8 to 3.9 mm a-1. A toy plastic pail and two radiocarbon ages from section Au05-1-00 reveal an increase in modern sedimentation rates from 1.6 to 14.3 mm a-1. This increase may have been caused by greater fluvial erosion from the large-scale introduction of European agricultural practices in the 19th century.